PBL AS AN ALTERNATIVE WAY TO ACQUIRE REAL LIFE SKILLS - Papoyan, Anna (International Journal of Innovative Technologies in Social Science, 2023)
Teaching a language is an ongoing hard process. The teacher’s task is to lead this process by applying interesting and innovative ways and approaches so that the learners (it doesn’t matter at school or higher educational institutions) would study not because they have to or their parents want them to, but they would study because they feel the flash of the intrinstic motivation. The teachers should do their best to bring the students body, mind and soul into the classroom by finding ways to turn students extrinsic motivation into inner desire enthusiasm and passion. Project Based Learning is a good means to get this destination if it is organized in the right way and it will become a magic tool in the hands of the smart master if applied effectively. The article highlights the necessity and ways to organize, manage and control this interesting journey full of real-life tasks and assignments.